Emergence of NK-cell progenitors and functionally competent NK-cell lineage subsets in the early mouse embryo. - Tang, Y; Peitzsch, C; Charoudeh, H; Cheng, M; Chaves, P; Jacobsen, SE; Sitnicka, E (2012)
The earliest stages of natural killer (NK)-cell development are not well characterized. In this study, we investigated in different fetal hematopoietic tissues how NK-cell progenitors and their mature NK-cell progeny emerge and expand during fetal development. Here we demonstrate, for the first time, that the counterpart of adult BM Lin(-)CD122(+)NK1.1(-)DX5(-) NK-cell progenitor (NKP) emerges in the fetal liver at E13.5. After NKP expansion, immature NK cells emerge at E14.5 in the liver and E15.5 in the spleen. Thymic NK cells arise at E15.5, whereas functionally competent cytotoxic NK cells were present in the liver and spleen at E16.5 and E17.5, respectively. Fetal NKPs failed to produce B and myeloid cells but sustained combined NK- and T-lineage potential at the single-cell level. NKPs were also found in the fetal blood, spleen, and thymus. These findings show the emergence and expansion of bipotent NK/T-cell progenitor during fetal and adult lymphopoiesis, further supporting that NK/T-lineage restriction is taking place prethymically. Uncovering the earliest NK-cell developmental stages will provide important clues, helping to understand the origin of diverse NK-cell subsets, their progenitors, and key regulators.